Career Adaptibility of Recent Graduates in The Modern Workplace: The Roles of Self-Efficacy and Social Support - Wikantiyoso, Bimo; Handayani, Fitri (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study investigates the role of self-efficacy and social support in enhancing career adaptability among recent graduates in the modern workplace, focusing on the Jakarta metropolitan area.  Recent graduates face significant challenges in leaping from academia to the professional world. Rapid technological advancements and a constantly evolving job market demand adaptability and resilience. As new graduates navigate this complex landscape, they often encounter uncertainty and ambiguity, making it crucial to possess the skills to adapt to changing circumstances This research uses a quantitative approach; data from 213 recent graduates were collected through an online questionnaire. The Career Adapt-Abilities Scale (CAAS), General Self-Efficacy Scale (GSE), and Multidimensional Scale of Perceived Social Support (MSPSS) were utilized toS measure the variables. Regression analysis revealed that both self-efficacy and social support have a significant positive impact on career adaptability. These findings underscore the importance of these two factors in assisting recent graduates in navigating complex and dynamic work environments. Moreover, the study highlights that recent graduates with high self-efficacy are more confident and adaptable in the workplace. Those with a strong sense of career control make more informed career decisions. While most participants demonstrated moderate adaptability, participants with high self-efficacy expressed a keen interest in career development and planning. Practical implications suggest that organizations should prioritize developing self-efficacy and providing robust social support systems to aid recent graduates in their career transitions.